2017
DOI: 10.1371/journal.pone.0182413
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of prehospital emergency medical services for hyperglycaemia: A community-based observational study

Abstract: AimsThis study examines prehospital Emergency Medical Service (EMS) utilisation and patterns of demand for hyperglycaemia management, including characteristics of individuals and factors related to hospital transport.Materials and methodsA state-wide, community-based observational study of all patients requiring prehospital EMS for hyperglycaemia during a 7 year study period (Jan 2009–Dec 2015) using electronic data from the Ambulance Victoria data warehouse was conducted. Pre-specified variables related to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In total, 11 studies reported on the incidence of hypoglycaemia in home-dwelling older people (Table 1 ) [ 30 32 , 36 , 37 , 39 , 42 , 44 , 47 , 50 , 51 ]. The majority of the studies reported data from ambulance records or emergency hospital visits [ 30 , 36 , 37 , 39 , 42 , 44 , 47 , 50 , 51 ], while one reported combined data of episodes of hypoglycaemia from outpatient visits, emergency departments and inpatient encounters with admission diagnosis hypoglycaemia [ 31 ]. Only one study reported observational data of mild, moderate and severe hypoglycaemia in home-dwelling older individuals registered by continuous glucose monitoring (CGM) [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 11 studies reported on the incidence of hypoglycaemia in home-dwelling older people (Table 1 ) [ 30 32 , 36 , 37 , 39 , 42 , 44 , 47 , 50 , 51 ]. The majority of the studies reported data from ambulance records or emergency hospital visits [ 30 , 36 , 37 , 39 , 42 , 44 , 47 , 50 , 51 ], while one reported combined data of episodes of hypoglycaemia from outpatient visits, emergency departments and inpatient encounters with admission diagnosis hypoglycaemia [ 31 ]. Only one study reported observational data of mild, moderate and severe hypoglycaemia in home-dwelling older individuals registered by continuous glucose monitoring (CGM) [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most studies reported incidences of hypoglycaemia requiring prehospital emergency medical care with or without hospital admission in patients with diabetes mellitus from 0.5–2.5 episodes/100 patient years [ 30 , 36 , 39 , 44 , 50 , 51 ]. The incidence of hypoglycaemia reported by Parsaik and colleagues with data from the US was somewhat higher; ambulance calls related to hypoglycaemia were performed in 9/100 individuals with type 2 diabetes and the calls for hypoglycaemia were 2% of the total number of calls for emergency assistance [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the period from January 2009 until December 2015. The SARIMA (0, 1, 0) × (0, 1, 0) 12 model provided the best fit model dealing with the number of patients [7].…”
Section: Literature Reviewmentioning
confidence: 99%